Evaluating the effect of various types of disinfectants on bacterial biofilms - Yu. K. Yushina; N. A. Nasyrov; E. V. Zaiko; M. A. Grudistova; M. D. Reshchikov (Теория и практика переработки мяса, 2023)
Biofilm formation on equipment surfaces is a potential food safety hazard, providing increased resistance and persistence of pathogens and spoilage microorganisms in food production environments. The issue of preventing the biofilm formation is extremely important, since a wide range of disinfectants does not always provide the proper effect. The article discusses the antimicrobial effectiveness of disinfectants with various active ingredients (based on active chlorine, peracetic acid and quaternary ammonium compounds (QAC) with enzymatic substances) on binary biofilms. The objects of the study were the strains of pathogenic and opportunistic microorganisms isolated from abiotic surfaces of food production environments and food products. Different effects of disinfectants on biofilms formed by bacteria have been established. Disinfectant based on peracetic acid and chlorine had the greatest effect on binary biofilms of Brochothrix thermosphacta/Salmonella spp. and Staphylococcus equorum/Salmonella spp. The greatest antimicrobial effect on biofilm of Listeria monocytogenes 12/Pseudomonas azotoformans 6 was shown by a chlorine-based disinfectant. Disinfectants based on chlorine and QAC with enzymatic substances were most effective against the binary biofilm of L. monocytogenes 12/Salmonella spp. 14. However, none of the disinfectants had absolute antimicrobial effectiveness against the studied binary biofilms. Biofilm-forming microorganisms have shown resistance to the recommended concentrations of disinfectants. Therefore, currently, it is extremely important to revise approaches to hygiene at enterprises by finding working concentrations of new antimicrobial agents and new procedure that are effective for destroying biofilms.